Lipoprotein(a) and Cardiovascular Outcomes in Patients with Previous Myocardial Infarction: A Prospective Cohort Study - Cao, Ye-Xuan; Zhang, Hui-Wen; Jin, Jing-Lu; Liu, Hui-Hui; Zhang, Yan; Zhang, Meng; Gao, Ying; Guo, Yuan-Lin; Wu, Na-Qiong; Zhu, Cheng-Gang; Dong, Qian; Sun, Jing; Wang, Le-Feng; Gao, Run-Lin; Li, Jian-Jun (Thrombosis and Haemostasis, 2021)
Lipoprotein(a) [Lp(a)] has been documented to be associated with atherothrombotic diseases. However, the prognostic impact of Lp(a) on long-term clinical outcomes among patients with previous myocardial infarction (MI) remains unclear. In this prospective cohort study, we consecutively enrolled 3,864 post-MI patients to assess the cardiovascular events (CVEs), including MI, ischemic stroke, and cardiac mortality. Lp(a) levels were determined using an immunoturbidimetry assay and the participants were categorized according to Lp(a) quartiles. The Cox proportional hazards model was used to calculate hazard ratios (HRs) with 95% confidence intervals (CIs). During a median follow-up of 4.1 years, 331 (8.6%) CVEs were identified. Lp(a) was significantly higher in patients with CVEs (25.17 [11.13–47.83] vs. 18.18 [7.90–40.30] mg/dL, p = 0.001). The cumulative rates of CVEs and cardiac mortality were significantly higher in patients with high Lp(a) levels (both log-rank p < 0.001). Multivariate Cox regression analysis showed a significant correlation between Lp (a) levels treated as a natural logarithm-transformed continuous variable and increased CVEs (adjusted HR:1.22, 95% CI:1.09–1.35, p = 0.001) or cardiac mortality (HR:1.30, 95% CI:1.14–1.48, p < 0.001). The addition of Lp(a) to a prognostic model revealed a significant improvement in C-statistic, net reclassification, and integrated discrimination. In conclusion, elevated levels of Lp(a) were indeed associated with long-term worse outcomes in patients with prior MI, suggesting a novel hint that the measurement of Lp(a) might help in risk stratification and future management in those high-risk individuals.
Keywords: Lipoprotein(a); myocardial infarction; cardiovascular events; cardiac mortality